ANALISIS FAKTOR PENGHAMBAT EKSPOR BAGI UKM DI KOTA DENPASAR - Wulandari, Anak Agung Ayu; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 5, Mei 2018 (pp. 868-1111), 2018)
The development of SMEs in Indonesia is still faced with various problems, causing weak competitiveness of imported products. Major issues facing SMEs are, among others, limited infrastructure and government access related to licensing and bureaucracy and high rates of levies. This study aims to analyze whether or not significant influence indirectly External factors are knowledge, resources, and procedures against exogenous and internal factors such as knowledge, resources, and procedure against export barriers. The result is: 1) Exogen positive and significant effect on knowledge. 2) Exogen positive and significant effect on resources. 3) Exogen positive and significant effect on the procedure. 4) Knowledge has a positive and significant effect on export barriers. 5) Resources have a positive and significant impact on export barriers. 6) Procedure has a positive and significant effect on export barriers.